PROBLEMATIKA HUKUM TERHADAP PRAKTIK TYING PADA PENJUALAN MINYAK GORENG MINYAKITA DI SAMARINDA - Arafah, Andi Zohrah Zahiroh; Arifudin, Nur; Pribadi, Deny Slamet (Universitas Labuhanbatu, 2025)
This study examines the practice of tying in the sale of the government-subsidized cooking oil